Au and Au-Based nanomaterials: Synthesis and recent progress in electrochemical sensor applications - Xiao, Ting; Huang, Jianshe; Wang, Dewen; Meng, Tian; Yang, Xiurong (Talanta (Oxford), 2020)
This review summarizes the synthesis of gold (Au) and Au-based nanomaterials and their recent advances of application in electrochemical small-molecule sensors, DNA sensors and immunosensors. Au nanoparticles with various shape and size have been synthesized by using physical, chemical, biological, electrochemical and seeding growth methods. In order to broaden the applications and improve the functionality of Au nanoparticles, numerous Au-based nanocomposite materials have been developed, including bimetallic nanoparticles, metal oxide-gold, polymer-gold, carbon nanotube-gold and graphene/graphene oxide-gold nanocomposites. Finally, the application of Au nanoparticles and Au-based nanocomposite materials in electrochemical sensors and their analytical performance were discussed. Electrochemical sensor applications of Au and Au-based nanomaterials. [Display omitted] •The morphology- and composition-controlled synthesis of Au and Au-based nanomaterials were discussed.•The application of Au and Au-based nanomaterials in electrochemical small-molecule sensors, DNA sensors and immunosensors was summarized.•This review emphasized on the features of different Au and Au-based nanomaterials as electrode materials for electrochemical sensing various analytes.